Buried interface molecular hybrid for inverted perovskite solar cells - Liu, Sanwan; Li, Jingbai; Xiao, Wenshan; Chen, Rui; Sun, Zhenxing; Zhang, Yong; Lei, Xia; Hu, Shuaifeng; Kober-Czerny, Manuel; Wang, Jianan; Ren, Fumeng; Zhou, Qisen; et al. (Nature (London), 2024)
Perovskite solar cells with an inverted architecture provide a key pathway for commercializing this emerging photovoltaic technology because of the better power conversion efficiency and operational stability compared with the normal device structure. Specifically, power conversion efficiencies of the inverted perovskite solar cells have exceeded 25% owing to the development of improved self-assembled molecules 1 – 5 and passivation strategies 6 – 8 . However, poor wettability and agglomeration of self-assembled molecules 9 – 12 cause interfacial losses, impeding further improvement in the power conversion efficiency and stability. Here we report a molecular hybrid at the buried interface in inverted perovskite solar cells that co-assembled the popular self-assembled molecule [4-(3,6-dimethyl-9 H -carbazol-9-yl)butyl]phosphonic acid (Me-4PACz) with the multiple aromatic carboxylic acid 4,4′,4″-nitrilotribenzoic acid (NA) to improve the heterojunction interface. The molecular hybrid of Me-4PACz with NA could substantially improve the interfacial characteristics. The resulting inverted perovskite solar cells demonstrated a record certified steady-state efficiency of 26.54%. Crucially, this strategy aligns seamlessly with large-scale manufacturing, achieving one of the highest certified power conversion efficiencies for inverted mini-modules at 22.74% (aperture area 11.1 cm 2 ). Our device also maintained 96.1% of its initial power conversion efficiency after more than 2,400 h of 1-sun operation in ambient air. High efficiency in perovskite solar cells is achieved by using a molecular hybrid of a self-assembled monolayer with nitrilotribenzoic acid.